2016
DOI: 10.1111/clr.12854
|View full text |Cite
|
Sign up to set email alerts
|

Marginal healing using Polyetheretherketone as healing abutments: an experimental study in dogs

Abstract: The coronal level of the hard and soft tissues allows the conclusion that the use of PEEK as healing abutments may be indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 17 publications
1
23
0
1
Order By: Relevance
“…Finally, 54 articles were included in present systematic review. Detailed data of the incorporated studies are listed as: 36 invitro studies in Table and 18 invivo studies in Table on PEEK material to find its efficacy as dental implant material .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 54 articles were included in present systematic review. Detailed data of the incorporated studies are listed as: 36 invitro studies in Table and 18 invivo studies in Table on PEEK material to find its efficacy as dental implant material .…”
Section: Resultsmentioning
confidence: 99%
“…PEEK abutments are recommended for fixed provisional restorations when the prosthesis has to remain in oral cavity for 1 to 3 months. Reinforced PEEK is emerging as an effective alternative to Ti abutments for preservation of soft tissue stability, bone height, and biocompatibility …”
Section: Discussionmentioning
confidence: 99%
“…However, PTVs were measured with just titanium healing abutments in these studies. Today, many manufacturers fabricate PEEK healing abutments as an alternative to titanium healing abutments because of their superior properties such as white color, biocompatibility, and ability to be shaped and modified . However no study exists evaluating the reliability of EPT devices when the PEEK healing abutments are used.…”
Section: Discussionmentioning
confidence: 99%
“…More recently healing abutments made of polymers such as polyetheretherketone (PEEK) which have been used in orthopedic surgery for over 20 years are introduced because of esthetic reasons and maintaining the health of peri‐implant soft tissues during healing. Although titanium healing abutments have been the gold standard in dental implant care for many years, it has been shown that PEEK may be preferred for the trans‐mucosal portion of the implant‐abutment complex during healing for esthetic or technical reasons . Several studies have confirmed the positive healing outcomes of PEEK healing abutments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation